Variation in Protein Intake Induces Variation in Spider Silk Expression - Blamires, Sean J.; Wu, Chun-Lin; Tso, I-Min (PLOS ONE, 2012)
Background It is energetically expensive to synthesize certain amino acids. The proteins (spidroins) of spider major ampullate (MA) silk, MaSp1 and MaSp2, differ in amino acid composition. Glutamine and proline are prevalent in MaSp2 and are expensive to synthesize. Since most orb web spiders express high proline silk they might preferentially attain the amino acids needed for silk from food and shift toward expressing more MaSp1 in their MA silk when starved. Methodology/Principal Findings We fed three spiders; Argiope aetherea, Cyrtophora moluccensis and Leucauge blanda, high protein, low protein or no protein solutions. A. aetherea and L. blanda MA silks are high in proline, while C. moluccesnsis MA silks are low in proline. After 10 days of feeding we determined the amino acid compositions and mechanical properties of each species' MA silk and compared them between species and treatments with pre-treatment samples, accounting for ancestry. We found that the proline and glutamine of A. aetherea and L. blanda silks were affected by protein intake; significantly decreasing under the low and no protein intake treatments. Glutmaine composition in C. moluccensis silk was likewise affected by protein intake. However, the composition of proline in their MA silk was not significantly affected by protein intake. Conclusions Our results suggest that protein limitation induces a shift toward different silk proteins with lower glutamine and/or proline content. Contradictions to the MaSp model lie in the findings that C. moluccensis MA silks did not experience a significant reduction in proline and A. aetherea did not experience a significant reduction in serine on low/no protein. The mechanical properties of the silks could not be explained by a MaSp1 expressional shift. Factors other than MaSp expression, such as the expression of spidroin-like orthologues, may impact on silk amino acid composition and spinning and glandular processes may impact mechanics.